Gly369Cys mutation in mouse FGFR3 causes achondroplasia by affecting both chondrogenesis and osteogenesis - Chen, Lin; Adar, Rivka; Yang, Xiao; Monsonego, Efrat O.; Li, Cuiling; Hauschka, Peter V.; Yayon, Avner; Deng, Chu-Xia (The Journal of Clinical Investigation, 1999)
Missense mutations in fibroblast growth factor receptor 3 (FGFR3) result in several human skeletal dysplasias, including the most common form of dwarfism, achondroplasia. Here we show that a glycine-to-cysteine substitution at position 375 (Gly375Cys) in human FGFR3 causes ligand-independent dimerization and phosphorylation of FGFR3 and that the equivalent substitution at position 369 (Gly369Cys) in mouse FGFR3 causes dwarfism with features mimicking human achondroplasia. Accordingly, homozygous mice were more severely affected than heterozygotes. The resulting mutant mice exhibited macrocephaly and shortened limbs due to retarded endochondral bone growth and premature closure of cranial base synchondroses. Compared with their wild-type littermates, mutant mice growth plates shared an expanded resting zone and narrowed proliferating and hypertrophic zones, which is correlated with the activation of Stat proteins and upregulation of cell-cycle inhibitors. Reduced bone density is accompanied by increased activity of osteoclasts and upregulation of genes that are related to osteoblast differentiation, including osteopontin, osteonectin, and osteocalcin. These data reveal an essential role for FGF/FGFR3 signals in both chondrogenesis and osteogenesis during endochondral ossification. J. Clin. Invest.104:1517–1525 (1999).